Strategi Mengoptimalkan Kinerja Guru Dengan Evaluasi Motivasi Dari Aspek Kompetensi Profesional,Kedesiplinan Dan Kecerdasan Emosi Pada Sekolah Menengah Pertama Negeri 2 Ampel Kabupaten Boyolali - Antik Suluh Sasanti; Siti Fatonah (STIE AUB Surakarta, 2026)
This research aims to analyze and determine strategies for optimizing teacher performance by evaluating motivation from the aspects of professional competence, discipline and emotional intelligence at State Junior High School 2 Ampel, Boyolali Regency. Data collected in this research was carried out by distributing questionnaires. This research uses reliability test analysis methods and validity tests, path analysis, t test, F test, and coefficient of determination test (R2). The sample in this research was 40 teachers at State Junior High School 2 Ampel, Boyolali Regency using census techniques. The research results show that teacher professional competence has a significant effect on teacher motivation. Teacher discipline has no significant effect on teacher motivation. Teacher emotional intelligence has no significant effect on teacher motivation. Teacher professional competence has a significant effect on teacher performance. Teacher discipline has no significant effect on teacher performance. Teacher emotional intelligence has a significant effect on teacher performance. Teacher motivation has a significant effect on teacher performance. The total R2 value is 0.503, meaning that the performance of teachers at 2 Ampel State Junior High School, Boyolali Regency is explained by professional competence, discipline, emotional intelligence and teacher motivation as intervining variables of 50.3% and the remaining 49.7% is explained by other variables outside the variables mentioned. examined in this research. The results of the simultaneous test (F test) on the first equation show that the value of F = 4.114, significance 0.013 < 0.05. The results of the simultaneous test (F test) on the second equation show that the value of F = 17.639, significance 0.000 < 0.05. The results of the path analysis by paying attention to the direct and indirect influences from the explanation above can be concluded that the direct influence of professional competence on teacher performance is the most dominant pathway.